Molybdenum-doped nano-zinc oxide loaded ordered mesoporous carbon adsorbent and preparation method and flue gas desulfurization application thereof

Through the preparation of molybdenum-doped nano zinc oxide-loaded orderly mesoporous carbon adsorbent, the problems of small sulfur capacity, unsatisfactory desulfurization accuracy and short life of zinc oxide-based adsorbents are solved, and efficient and stable flue gas desulfurization effect is achieved.

CN119386815AActive Publication Date: 2025-02-07XI AN JIAOTONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411553173.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing zinc oxide-based adsorbents have problems such as small sulfur capacity, poor desulfurization accuracy and short service life in coal chemical exhaust treatment.

Method used

Molybdenum-doped nano zinc oxide is used to load an ordered mesoporous carbon adsorbent. The preparation method includes preparing ordered micromesoporous carbon nanospheres, mixing aqueous solutions of zinc and molybdenum sources, adding urea and ordered micromesoporous carbon nanospheres , hydrothermal treatment and uniform precipitation were carried out to obtain a composite material loaded with 20 wt% ZnO-MoO3.

Benefits of technology

The sulfur capacity and desulfurization accuracy of the adsorbent are improved, and its life span is extended, achieving efficient and stable flue gas desulfurization effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119386815A_ABST
    Figure CN119386815A_ABST
Patent Text Reader

Abstract

The invention discloses a molybdenum-doped nano-zinc oxide loaded ordered mesoporous carbon adsorbent as well as a preparation method and flue gas desulfurization application thereof, and belongs to the technical field of preparation of ordered mesoporous carbon composite materials. The ordered micro-mesoporous carbon nanospheres with high specific surface area are selected as carriers, molybdenum-doped nano-zinc oxide is selected as an active component, hydrogen sulfide gas remaining in pores can be efficiently removed, the preparation conditions of the method are simple and controllable, and the prepared molybdenum-doped nano-zinc oxide loaded ordered mesoporous carbon adsorbent has a good application prospect. The defects of small sulfur capacity, non-ideal desulfurization precision, short service life and the like of the traditional zinc oxide desulfurizer are broken through, and the zinc oxide desulfurizer has high efficiency, economical efficiency and stability, so that the zinc oxide desulfurizer can be widely applied to the field of flue gas desulfurization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of ordered mesoporous carbon composite materials, and specifically relates to a molybdenum-doped nano zinc oxide-loaded ordered mesoporous carbon adsorbent that can be applied to industrial waste gas treatment and environmental protection, and a preparation method thereof and flue gas desulfurization application. Background Art

[0002] In a typical coal gasification process, the tail gas of the purification unit contains trace amounts of sulfides, which will cause varying degrees of environmental pollution if directly discharged into the atmosphere. At the same time, the sulfur substances and water vapor in the tail gas components are prone to attack the catalyst used in tail gas treatment, causing catalyst poisoning and ultimately catalyst deactivation. At present, the main desulfurizer for coal chemical tail gas treatment at home and abroad is zinc oxide, but its efficiency needs to be further improved. Therefore, modifying zinc oxide and constructing composite materials have certain application prospects and scientific research significance.

[0003] Metal doping is usually an effective strategy to improve the room temperature desulfurization performance of ZnO. For example, Bezverkhyy et al. found that Cu + During the desulfurization process, doping ZnO increases the concentration of sulfur vacancies in ZnS due to the “charge compensation effect”, which accelerates the S 2- With O 2- The exchange rate of ZnO increased, thereby improving the desulfurization performance of ZnO. Yang et al. found that Ni 2+ Doping ZnO can increase the concentration of oxygen vacancies, promote the hydroxylation of ZnO surface and HS - / S 2- With O 2- The exchange rate of Co 2+ It is also often used as a dopant to adjust the desulfurization performance of ZnO. Baird et al. prepared Co-doped ZnO desulfurizer by impregnation and coprecipitation. Through penetration experiments, it was shown that Co doping can improve the dispersibility of ZnO and increase the specific surface area of ​​ZnO, which is beneficial to improve the removal ability of ZnO for H2S. Wang D et al. used Mo-doped iron-based adsorbent to significantly increase the penetration time of hydrogen sulfide adsorption. Chen Y et al. doped ordered mesoporous carbon with zinc oxide / nitrogen. At room temperature and pressure, ordered mesoporous carbon as a carrier can improve the removal ability of ZnO for H2S.

[0004] From the above, we can see that although there are many new zinc oxide-based desulfurization adsorbents, due to the technical problems of small sulfur capacity, unsatisfactory desulfurization accuracy and short life of pre-desulfurizers in coal conversion and purification units, it is necessary to develop desulfurization materials that meet the above application scenarios in a targeted manner. It is still a key technical problem to be solved to find out the combination mode of pre-desulfurizer and sulfur, to improve the sulfur capacity of pre-desulfurizer and extend its life, and to develop efficient and stable desulfurization materials. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a molybdenum-doped nano-zinc oxide loaded ordered mesoporous carbon adsorbent and its preparation method and flue gas desulfurization application, so as to solve the technical problems of existing zinc oxide-based adsorbent materials with low sulfur capacity, unsatisfactory desulfurization accuracy and short life.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The invention discloses a method for preparing a molybdenum-doped nano zinc oxide-loaded ordered mesoporous carbon adsorbent, comprising the following steps:

[0008] 1) Preparation of ordered micro-mesoporous carbon nanospheres OM-CNS;

[0009] 2) dissolving a zinc source and a molybdenum source in water to obtain corresponding aqueous solutions, mixing the two aqueous solutions thoroughly, and then adding urea to obtain a mixed solution;

[0010] 3) Adding the ordered micro-mesoporous carbon nanospheres OM-CNS prepared in step 1) into the mixed solution, and then performing a hydrothermal treatment, and then performing a uniform precipitation treatment to obtain a molybdenum-doped nano-zinc oxide-loaded ordered mesoporous carbon adsorbent.

[0011] Preferably, in step 1), a soft template method is used to prepare ordered micro-mesoporous carbon nanospheres OM-CNS, comprising:

[0012] A low molecular weight phenolic resin is prepared, and an aqueous solution containing the thermosensitive hydrogel Pluronic F127 is added thereto, the mixture is stirred evenly, diluted with water and stirred continuously until precipitation occurs, and the reaction is stopped;

[0013] The reaction solution was heat treated at 120-140° C. for 24 hours, the precipitate was collected by filtration, washed, dried, and then carbonized to remove the copolymer template to obtain ordered micro-mesoporous carbon nanospheres OM-CNS.

[0014] More preferably, the low molecular weight phenolic resin refers to a phenolic resin with a molecular weight of 800 to 1200 Da.

[0015] Further preferably, the low molecular weight phenolic resin is prepared by the following method:

[0016] Phenol, formalin aqueous solution and NaOH aqueous solution are mixed in a volume ratio of 3:10:70-80, and stirred evenly at 60-80° C. to prepare a low molecular weight phenolic resin.

[0017] Further preferably, the ratio of Pluronic F127 to water in the aqueous solution containing the thermosensitive hydrogel Pluronic F127 is 0.96 g: (10-20) mL; the solution is stirred evenly at 60-70° C. for 2 h at a speed of 300-400 rpm; water is added to dilute the solution under stirring, and then stirring is continued at 60-70° C. until a small amount of precipitation occurs, i.e., the reaction is stopped.

[0018] More preferably, stirring treatment is performed at 66° C., which provides energy to accelerate the reaction rate without damaging the material.

[0019] Further preferably, in step 2), the zinc source is Zn(NO3)2·6H2O, and the molybdenum source is Mo(NO3)3·5H2O; wherein, the dosage ratio of Zn(NO3)2·6H2O and water is 0.002 mol:100 mL, and the dosage ratio of Mo(NO3)3·5H2O and water is (0.0002-0.001) mol:100 mL.

[0020] Preferably, in step 2), the molar ratio of urea to total metal ions (Zn, Mo) is (3.40-3.50):1.

[0021] Preferably, in step 3), the hydrothermal treatment is carried out at 120-150° C. for 16-24 h; the carbonization treatment to remove the copolymer template Pluronic F127 (polyethylene glycol-polypropylene glycol-polyethylene glycol (PEG-PPO-PEG) triblock copolymer) is carried out at 700° C. and carbonized for 2 h at a N2 flow rate of 200 mL / min.

[0022] The invention discloses a molybdenum-doped nano zinc oxide-loaded ordered mesoporous carbon adsorbent prepared by the above-mentioned preparation method. The adsorbent is loaded with 20 wt% of ZnO-MoO3.

[0023] Preferably, the chemical formula of the adsorbent is MoxZn1-x / OM, wherein Mo and Zn represent MoO3 and ZnO, respectively, OM represents an ordered micro-mesoporous carbon nanosphere carrier, and x represents the molar ratio of Mo / (Mo+Zn);

[0024] Further preferably, the gradient is set to Mo 0.1 Zn 0.9 / OM、Mo 0.2 Zn 0.8 / OM、Mo 0.3 Zn 0.7 / OM、Mo 0.4 Zn 0.6 / OM and Mo 0.5 Zn 0.5 / OM.

[0025] The invention discloses application of the molybdenum-doped nano zinc oxide-loaded ordered mesoporous carbon adsorbent in flue gas desulfurization.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The invention discloses a method for preparing a composite material of molybdenum-doped nano zinc oxide loaded with ordered mesoporous carbon. Ordered micro-mesoporous carbon nanospheres with a high specific surface area are selected as carriers, which can adsorb hydrogen sulfide gas generated in coal chemical industry to the greatest extent. Molybdenum-doped nano zinc oxide is used as an active component, which can efficiently remove the hydrogen sulfide gas retained in the pores. The preparation conditions are simple and controllable. The prepared molybdenum-doped nano zinc oxide loaded with ordered mesoporous carbon adsorbent overcomes the defects of traditional zinc oxide desulfurizers, such as small sulfur capacity, unsatisfactory desulfurization accuracy, short life and other technical problems. It has high efficiency, economy and stability, and can therefore be widely used in the field of flue gas desulfurization. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a physical picture of the ordered mesoporous carbon supported by molybdenum-doped nano-zinc oxide prepared in Example 3;

[0029] Figure 2 This is a physical picture of the ordered mesoporous carbon supported by molybdenum-doped nano-zinc oxide prepared in Example 3;

[0030] Figure 3-1 This is a test diagram of the activity of the molybdenum-doped nano-zinc oxide-supported ordered mesoporous carbon adsorbing hydrogen sulfide obtained in Example 3, with respect to the change in volume concentration;

[0031] Figure 3-2 This is a test graph of the activity of the molybdenum-doped nano-zinc oxide-supported ordered mesoporous carbon adsorbing hydrogen sulfide prepared in Example 3, with respect to the change in mass concentration;

[0032] Figure 3-3 This is the activity test diagram of the molybdenum-doped nano-zinc oxide-supported ordered mesoporous carbon adsorbing hydrogen sulfide prepared in Example 3, which is about the sulfur capacity change result;

[0033] Figure 4 This is the SEM image of the ordered mesoporous carbon loaded with molybdenum-doped nano-zinc oxide in Example 3. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0035] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0036] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0037] The present invention provides a method for preparing Mo-doped nano ZnO loaded on ordered mesoporous carbon, comprising the following steps:

[0038] 1) Using the soft template method and uniform precipitation method, 0.6 mL of phenol, 2.0 mL of formalin aqueous solution and 15 mL of NaOH aqueous solution (0.1 M) were mixed and stirred at 70° C. for 0.5 h to obtain a low molecular weight (800-1200 Da) phenolic resin.

[0039] 2) Then, a solution containing 0.96 g F127 and 15 mL H2O was added and stirred at 66°C for 2 h at a speed of 350 rpm. Then, 50 mL of water was added to dilute the solution under stirring. The resulting solution was stirred continuously at 66°C for 12 h until a small amount of sedimentation occurred, and then the reaction was immediately stopped.

[0040] 3) Take 20 mL of the obtained solution and 60 mL of water and transfer them into an autoclave, heat at 130°C for 24 h, collect by filtration, wash with distilled water several times, and dry at room temperature. Carbonize at 700°C for 2 h under N2 flow (200 mL / min) to remove the triblock copolymer template F127 (polyethylene glycol-polypropylene glycol-polyethylene glycol (PEG-PPO-PEG) triblock copolymer). Finally, an ordered mesoporous carbon sample (OM-CNS) was obtained.

[0041] 4) Using the uniform precipitation method, weigh appropriate amounts of Zn(NO3)2·6H2O and Mo(NO3)3.5H2O and dissolve them in 100 mL of deionized water, mix the above solutions thoroughly, and then add appropriate amounts of urea. The molar ratio of urea to total metal ions is 3.45:1. After the above solutions are thoroughly mixed, add 0.8 g of ordered micro-mesoporous carbon nanospheres (OM-CNS), put the mixed solution into a high-pressure reactor, heat to 108°C for 1 hour, age for 1 hour, filter and wash the obtained precursor, and dry it at 120°C for 2 hours. Mo-modified nano-ZnO was obtained as the active component by calcining at 270°C under N2 protection in a muffle furnace, and a series of ZnO-MoO3 co-loaded ordered micro-mesoporous carbon nanosphere adsorbents with a fixed load of 20wt.% were synthesized.

[0042] 5) The synthesized adsorbent is recorded as MoxZn1-x / OM, where Mo and Zn represent MoO3 and ZnO respectively, OM represents the ordered micro-mesoporous carbon nanosphere carrier, and x represents the molar ratio of Mo / (Mo+Zn). The gradient is set as (Mo0Zn1 / OM, Mo 0.1 Zn 0.9 / OM、Mo 0.2 Zn 0.8 / OM、Mo 0.3 Zn 0.7 / OM、Mo 0.4 Zn 0.6 / OM、Mo 0.5 Zn 0.5 / OM, Mo1Zn0 / OM).

[0043] Example 1

[0044] (1) Weigh 0.1g of Mo(NO3)3·5H2O and 0.73g of Zn(NO3)2·6H2O and dissolve them in 100mL of deionized water. After mixing the above solutions thoroughly, add 0.56g of urea. The molar ratio of urea to total metal ions is 3.45:1. After mixing the above solutions thoroughly, add 0.8g of ordered micro-mesoporous carbon nanospheres (OM-CNS). Put the mixed solution into a high-pressure reactor, heat it to 108℃ for 1h, age it for 1h, filter and wash the obtained precursor, and dry it at 120℃ for 2h. After calcining at 270℃ for 1h under N2 protection in a muffle furnace, Mo-modified nano-ZnO was obtained as the active component and ordered micro-mesoporous carbon nanospheres were used as the carrier of the desulfurizer. A series of ZnO-MoO3 co-loaded ordered micro-mesoporous carbon nanosphere adsorbents with a fixed zinc oxide loading of 20wt.% were synthesized.

[0045] (2) The synthesized adsorbent is denoted as Mo x Zn 1-x / OM, where Mo and Zn represent MoO3 and ZnO respectively, and OM represents ordered micro-mesoporous carbon nanosphere carrier. The desulfurizer prepared this time is named Mo 0.1 Zn 0.9 / OM.

[0046] Example 2

[0047] (1) Weigh 0.23g of Mo(NO3)3·5H2O and 0.73g of Zn(NO3)2·6H2O and dissolve them in 100mL of deionized water. After the above solutions are fully mixed, 0.64g of urea is added. The molar ratio of urea to total metal ions is 3.45:1. After the above solutions are fully mixed, 0.8g of ordered micro-mesoporous carbon nanospheres (OM-CNS) are added, and the mixed solution is placed in a high-pressure reactor, heated to 108℃ for reaction for 1h, aged for 1h, and the obtained precursor is filtered, washed, and dried at 120℃ for 2h. Mo-modified nano-ZnO as the active component and ordered micro-mesoporous carbon nanospheres as the carrier are obtained by calcining at 270℃ under N2 protection in a muffle furnace for 1h. A series of ZnO-MoO3 co-loaded ordered micro-mesoporous carbon nanosphere adsorbents with a fixed loading of 20wt.% are synthesized.

[0048] (2) The synthesized adsorbent is denoted as Mo x Zn 1-x / OM, where Mo and Zn represent MoO3 and ZnO respectively, and OM represents ordered micro-mesoporous carbon nanosphere carrier. The desulfurizer prepared this time is named Mo 0.2 Zn 0.8 / OM.

[0049] Example 3

[0050] (1) Weigh 0.40g of Mo(NO3)3·5H2O and 0.73g of Zn(NO3)2·6H2O and dissolve them in 100mL of deionized water. After the above solutions are fully mixed, 0.73g of urea is added. The molar ratio of urea to total metal ions is 3.45:1. After the above solutions are fully mixed, 0.8g of ordered micro-mesoporous carbon nanospheres (OM-CNS) are added, and the mixed solution is placed in a high-pressure reactor, heated to 108℃ for reaction for 1h, aged for 1h, and the obtained precursor is filtered, washed, and dried at 120℃ for 2h. Mo-modified nano-ZnO as the active component and ordered micro-mesoporous carbon nanospheres as the carrier are obtained by calcining at 270℃ under N2 protection in a muffle furnace for 1h. A series of ZnO-MoO3 co-loaded ordered micro-mesoporous carbon nanosphere adsorbents with a fixed loading of 20wt.% are synthesized.

[0051] (2) The synthesized adsorbent is denoted as Mo x Zn 1-x / OM, where Mo and Zn represent MoO3 and ZnO respectively, and OM represents ordered micro-mesoporous carbon nanosphere carrier. The desulfurizer prepared this time is named Mo 0.3 Zn 0.7 / OM.

[0052] The actual picture of the ordered mesoporous carbon loaded with molybdenum-doped nano zinc oxide prepared in this embodiment is as follows: Figure 1 and Figure 2 As shown in the SEM images Figure 4 shown.

[0053] Example 4

[0054] (1) Weigh 0.61g of Mo(NO3)3·5H2O and 0.73g of Zn(NO3)2·6H2O and dissolve them in 100mL of deionized water. After mixing the above solutions thoroughly, add 0.85g of urea. The molar ratio of urea to total metal ions is 3.45:1. After mixing the above solutions thoroughly, add 0.8g of ordered micro-mesoporous carbon nanospheres (OM-CNS). Put the mixed solution into a high-pressure reactor, heat it to 108℃ for 1h, age it for 1h, filter and wash the obtained precursor, and dry it at 120℃ for 2h. The desulfurizer with Mo-modified nano-ZnO as the active component and ordered micro-mesoporous carbon nanospheres as the carrier was obtained by calcining at 270℃ under N2 protection in a muffle furnace for 1h. A series of ZnO-MoO3 co-loaded ordered micro-mesoporous carbon nanosphere adsorbents with a fixed loading of 20wt.% were synthesized.

[0055] (2) The synthesized adsorbent is denoted as Mo x Zn 1-x / OM, where Mo and Zn represent MoO3 and ZnO respectively, and OM represents ordered micro-mesoporous carbon nanosphere carrier. The desulfurizer prepared this time is named Mo 0.4 Zn 0.6 / OM.

[0056] Example 5

[0057] (1) Weigh 0.92g of Mo(NO3)3·5H2O and 0.73g of Zn(NO3)2·6H2O and dissolve them in 100mL of deionized water. After the above solutions are fully mixed, 1.02g of urea is added. The molar ratio of urea to total metal ions is 3.45:1. After the above solutions are fully mixed, 0.8g of ordered micro-mesoporous carbon nanospheres (OM-CNS) are added, and the mixed solution is placed in a high-pressure reactor, heated to 108℃ for reaction for 1h, aged for 1h, and the obtained precursor is filtered, washed, and dried at 120℃ for 2h. Mo-modified nano-ZnO as the active component and ordered micro-mesoporous carbon nanospheres as the carrier are obtained by calcining at 270℃ under N2 protection in a muffle furnace for 1h. A series of ZnO-MoO3 co-loaded ordered micro-mesoporous carbon nanosphere adsorbents with a fixed loading of 20wt.% are synthesized.

[0058] (2) The synthesized adsorbent is denoted as Mo x Zn 1-x / OM, where Mo and Zn represent MoO3 and ZnO respectively, and OM represents ordered micro-mesoporous carbon nanosphere carrier. The desulfurizer prepared this time is named Mo 0.5 Zn 0.5 / OM.

[0059] Comparative Example 1

[0060] (1) Weigh 0g of Mo(NO3)3·5H2O and 0.73g of Zn(NO3)2·6H2O and dissolve them in 100mL of deionized water respectively. After the above solutions are fully mixed, 0.51g of urea is added. The molar ratio of urea to total metal ions is 3.45:1. After the above solutions are fully mixed, 0.8g of ordered micro-mesoporous carbon nanospheres (OM-CNS) are added, and the mixed solution is placed in a high-pressure reactor, heated to 108℃ for reaction for 1h, aged for 1h, and the obtained precursor is filtered, washed, and dried at 120℃ for 2h. After calcination at 270℃ for 1h under N2 protection in a muffle furnace, Mo-modified nano-ZnO is obtained as the active component and ordered micro-mesoporous carbon nanospheres are used as the carrier of the desulfurizer. A series of ZnO-MoO3 co-loaded ordered micro-mesoporous carbon nanosphere adsorbents with a fixed loading of 20wt.% are synthesized.

[0061] (2) The synthesized adsorbent is denoted as Mo x Zn 1-x / OM, where Mo and Zn represent MoO3 and ZnO respectively, and OM represents ordered micro-mesoporous carbon nanosphere carrier. The desulfurizer prepared this time is named Mo0Zn1 / OM.

[0062] Comparative Example 2

[0063] (1) Weigh 0.52g of Mo(NO3)3·5H2O and 0g of Zn(NO3)2·6H2O and dissolve them in 100mL of deionized water respectively. After the above solutions are fully mixed, 0.29g of urea is added. The molar ratio of urea to total metal ions is 3.45:1. After the above solutions are fully mixed, 0.8g of ordered micro-mesoporous carbon nanospheres (OM-CNS) are added, and the mixed solution is placed in a high-pressure reactor, heated to 108℃ for reaction for 1h, aged for 1h, and the obtained precursor is filtered, washed, and dried at 120℃ for 2h. Mo-modified nano-ZnO as the active component and ordered micro-mesoporous carbon nanospheres as the carrier are obtained by calcining at 270℃ under N2 protection in a muffle furnace for 1h. A series of ZnO-MoO3 co-loaded ordered micro-mesoporous carbon nanosphere adsorbents with a fixed loading of 20wt.% are synthesized.

[0064] (2) The synthesized adsorbent is denoted as Mo x Zn 1-x / OM, where Mo and Zn represent MoO3 and ZnO respectively, and OM represents ordered micro-mesoporous carbon nanosphere carrier. The desulfurizer prepared this time is named Mo1Zn0 / OM.

[0065] The desulfurizers prepared in Example 3, Comparative Example 1 and Comparative Example 2 are selected below to test the activity of adsorbing hydrogen sulfide on ordered mesoporous carbon supported by molybdenum-doped nano zinc oxide, mainly for the test of desulfurization performance:

[0066] The desulfurization test of the desulfurizer was carried out in the VOCs generation and reaction device of Tianda Beiyang Chemical Experimental Equipment Company, and the inner diameter of the reactor was 8mm. The prepared samples were ground and sieved, and samples with a particle size of 40-60 mesh were selected and loaded into the reactor. The sample loading mass was 0.2g, and the desulfurization reaction conditions were normal temperature and pressure. The concentration of inlet H2S was 100ppm (0.2% H2S and carrier gas N2), and the gas flow rate was 200mL / min. When the outlet H2S concentration reached 10ppm of the inlet concentration, it was considered to be penetrated; when the H2S concentration in the inlet and outlet gases was the same, the sample reached adsorption saturation and the experiment was stopped. The H2S concentration at the inlet and outlet of the Fuli gas chromatograph GC9790Ⅱ was used for detection and analysis. The breakthrough sulfur capacity and saturated sulfur capacity of the desulfurizer were calculated by integrating the breakthrough curve of the desulfurizer.

[0067] like Figure 3-1 , Figure 3-2 and Figure 3-3 As shown in the desulfurization curve and sulfur capacity diagram, compared with the comparative desulfurizers Mo0Zn1 / OM (Comparative Example 1) and Mo1Zn0 / OM (Comparative Example 2), Mo 0.3 Zn 0.7 / OM has better desulfurization performance, Mo 0.3 Zn 0.7 / OM desulfurizer began to penetrate at 30min and completely penetrated at 80min, the saturated sulfur capacity reached 7.38mg / g, and the breakthrough sulfur capacity was 4.56mg / g. In the comparative example, the desulfurization performance of Mo0Zn1 / OM was slightly better than that of Mo1Zn0 / OM.

[0068] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a molybdenum-doped nano zinc oxide-loaded ordered mesoporous carbon adsorbent, characterized in that: The following steps are involved: 1) Preparation of ordered micro-mesoporous carbon nanospheres OM-CNS; 2) dissolving a zinc source and a molybdenum source in water to obtain corresponding aqueous solutions, mixing the two aqueous solutions thoroughly, and then adding urea to obtain a mixed solution; 3) adding the ordered micro-mesoporous carbon nanospheres OM-CNS prepared in step 1) into the mixed solution, and then performing a hydrothermal treatment, and then a uniform precipitation treatment to obtain a molybdenum-doped nano-zinc oxide-loaded ordered mesoporous carbon adsorbent.

2. The method for preparing the molybdenum-doped nano zinc oxide-loaded ordered mesoporous carbon adsorbent according to claim 1, characterized in that: In step 1), a soft template method is used to prepare ordered micro-mesoporous carbon nanospheres OM-CNS, comprising: A low molecular weight phenolic resin is prepared, and an aqueous solution containing the thermosensitive hydrogel Pluronic F127 is added thereto, the mixture is stirred evenly, diluted with water and stirred continuously until precipitation occurs, and the reaction is stopped; The reaction solution was heat treated at 120-140° C. for 24 hours, the precipitate was collected by filtration, washed, dried, and then carbonized to remove the copolymer template to obtain ordered micro-mesoporous carbon nanospheres OM-CNS.

3. The method for preparing the molybdenum-doped nano zinc oxide-loaded ordered mesoporous carbon adsorbent according to claim 2, characterized in that: Low molecular weight phenolic resin is prepared by the following method: Phenol, formalin aqueous solution and NaOH aqueous solution are mixed in a volume ratio of 3:10:70-80, and stirred evenly at 60-80° C. to prepare a low molecular weight phenolic resin.

4. The method for preparing the molybdenum-doped nano zinc oxide-loaded ordered mesoporous carbon adsorbent according to claim 2, characterized in that: The aqueous solution containing the thermosensitive hydrogel Pluronic F127 has a dosage ratio of Pluronic F127 to water of 0.96 g: (10-20) mL; the solution is stirred evenly at 60-70° C. for 2 hours at a rotation speed of 300-400 rpm; water is added to dilute the solution under stirring, and then the solution is continuously stirred at 60-70° C. until precipitation occurs, thereby stopping the reaction.

5. The method for preparing the desulfurizer of molybdenum-doped nano zinc oxide loaded with ordered mesoporous carbon according to claim 1, characterized in that: In step 2), the zinc source is Zn(NO3)2·6H2O, and the molybdenum source is Mo(NO3)3·5H2O; wherein, the dosage ratio of Zn(NO3)2·6H2O to water is 0.002mol:100mL, and the dosage ratio of Mo(NO3)3·5H2O to water is (0.0002-0.001mol):100mL.

6. The method for preparing the molybdenum-doped nano zinc oxide-loaded ordered mesoporous carbon adsorbent according to claim 1, characterized in that: In step 2), the molar ratio of urea to the total metal ions of the zinc and molybdenum sources is 3.4-3.5:

1.

7. The method for preparing the molybdenum-doped nano zinc oxide-loaded ordered mesoporous carbon adsorbent according to claim 1, characterized in that: In step 3), the hydrothermal treatment is carried out at 120-150° C. for 16-24 h; the carbonization treatment to remove the copolymer template Pluronic F127 is carried out at 700° C. for 2 h at a N2 flow rate of 200 mL / min.

8. The molybdenum-doped nano zinc oxide-loaded ordered mesoporous carbon adsorbent prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The adsorbent is loaded with 20 wt% ZnO-MoO3.

9. The molybdenum-doped nano zinc oxide-loaded ordered mesoporous carbon adsorbent according to claim 8, characterized in that: The chemical formula of the adsorbent is MoxZn1-x / OM, where Mo and Zn represent MoO3 and ZnO, respectively, OM represents an ordered micro-mesoporous carbon nanosphere carrier, and x represents the molar ratio of Mo / (Mo+Zn); Set the gradient to Mo 0.1 Zn 0.9 / OM、Mo 0.2 Zn 0.8 / OM、Mo 0.3 Zn 0.7 / OM、Mo 0.4 Zn 0.6 / OM and Mo 0.5 Zn 0.5 / OM.

10. Use of the molybdenum-doped nano zinc oxide-loaded ordered mesoporous carbon adsorbent according to claim 8 or 9 in flue gas desulfurization.

Citation Information

Patent Citations

  • Gasoline desulfurization adsorbent and preparation method thereof

    CN104741079A

  • Composite material, its manufacture and use in gas purification

    CN109310981A

  • Ion separation used kelvin water dropper

    KR1020200145521A